Physics of Anisotropic Compact Star Models with Observational Data - Saha , Pameli; Debnath , Ujjal (Current Perspective to Physical Science Research Vol. 2, 2023)
The anisotropic component for studying dense objects like strange stars, compact objects, etc. has become diverse in Astrophysics. This chapter aims to analyze the physical behavior of some anisotropic compact star models in the back- ground of a quintessence dark energy field. Next, we acquire the equations of motion with the electromagnetic field and modified Chaplygin gas in f(T) gravity. Then matching conditions have been highlighted to discuss anisotropic behavior, stability of energy conditions, stability analysis with adiabatic index, mass, compactness, and surface redshift. It also observes the maximum energy density and radial pressure values for different compact stars. Finally, it is correlated with the experiential data in cases of various types of compact stars.